2013
DOI: 10.1103/physreva.88.053412
|View full text |Cite
|
Sign up to set email alerts
|

Resonant enhancement of the harmonic-generation spectrum of beryllium

Abstract: The high-order harmonic-generation (HHG) spectrum of Be is investigated in the multiphoton regime by solving the full-dimensional, two-active-electron, time-dependent Schrödinger equation in an intense (≈10 13 W/cm 2 ), 30-cycle laser field. As the laser frequency ω L varies from 1.7 to 1.8 eV (which is in the tunable range of a Ti:sapphire laser), the seventh harmonic becomes resonant sequentially with the transition between the ground state and two doubly excited autoionizing states, 2p4s( 1 P ) (at ω L = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…With the addition of 1s 3s 2 and 1s 3p 2 states, a structure similar to the one predicted by the benchmark calculation develops around 10 eV. This structure may be identified with the lowest resonance 1s 2p3s 2 at 10.71 eV [6]. The coupled channels calculations with the number of ionic states considered here, however do not reproduce the structure on the second peak exactly.…”
Section: Berylliummentioning
confidence: 48%
See 2 more Smart Citations
“…With the addition of 1s 3s 2 and 1s 3p 2 states, a structure similar to the one predicted by the benchmark calculation develops around 10 eV. This structure may be identified with the lowest resonance 1s 2p3s 2 at 10.71 eV [6]. The coupled channels calculations with the number of ionic states considered here, however do not reproduce the structure on the second peak exactly.…”
Section: Berylliummentioning
confidence: 48%
“…This allows us to have a benchmark for our spectra by adapting the simple Coulomb potential to an effective potential in our two electron code. We use the effective potential given in [6] for our benchmark calculations. We refer to these as 'effective-2e' calculations.…”
Section: Berylliummentioning
confidence: 99%
See 1 more Smart Citation
“…In these works for atoms the three-dimensional time-dependent Schrödinger equation (TDSE) is solved using the single-active-electron approximation. General formulations for single ionization of an atom [25] and double ionization of He [29] by an arbitrarily polarized, few-cycle XUV pulse using perturbation theory (PT) have been validated numerically only for the case of a linearly polarized pulse [29][30][31][32] owing to its axial symmetry, which reduces the numerical effort. None of these many prior numerical investigations has addressed the challenging six-dimensional problem of a two-electron system interacting with an arbitrarily polarized XUV pulse.…”
mentioning
confidence: 99%
“…It has been shown that excited states play a role in high harmonic generation and enhancement [22][23][24][25]. In this work, we explore the feasibility of selective control over the domination of the two quantum pathways by populating different excited states of single He + ion to significantly enhance the HHG yield and cutoff extension, leading to the generation of intense and isolated ultra-short attosecond pulses.…”
mentioning
confidence: 99%